The Effect of Product Quality and Restaurant Atmosphere on Customer Loyalty: The Mediating Role of Customer Satisfaction at King Salman Restaurant - Christiana Kartika; Damelia Basauli Tambunan; Fahrul Riza (Jurnal Ilmiah Hospitality Management, 2026)
This study examines the influence of product quality and restaurant atmosphere on customer loyalty, with customer satisfaction as a mediating variable, at King Salman Restaurant in Kudus City, which offers Arabic and Indian cuisine. The research addresses increasing competition in the culinary industry, where retaining loyal customers is critical for sustainability. A causal quantitative approach was applied by collecting data from 140 dine-in customers selected through purposive sampling. All variables were measured using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that product quality has a positive and significant effect on customer satisfaction, while restaurant atmosphere does not significantly influence customer satisfaction. Furthermore, customer satisfaction partially mediates the relationship between product quality and customer loyalty. These findings highlight the importance of maintaining consistent food quality and a comfortable dining environment to enhance customer loyalty in restaurant businesses.